Management of the General Process of Parenteral Nutrition Using mHealth Technologies: Evaluation and Validation Study - Cervera Peris, Mercedes; Alonso Rorís, Víctor Manuel; Santos Gago, Juan Manuel; Álvarez Sabucedo, Luis; Wanden-Berghe, Carmina; Sanz-Valero, Javier (JMIR Publications, 2018)
BackgroundAny system applied to the control of parenteral nutrition (PN) ought to prove that the process meets the established requirements and include a repository of records to allow evaluation of the information about PN processes at any time. ObjectiveThe goal of the research was to evaluate the mobile health (mHealth) app and validate its effectiveness in monitoring the management of the PN process. MethodsWe studied the evaluation and validation of the general process of PN using an mHealth app. The units of analysis were the PN bags prepared and administered at the Son Espases University Hospital, Palma, Spain, from June 1 to September 6, 2016. For the evaluation of the app, we used the Poststudy System Usability Questionnaire and subsequent analysis with the Cronbach alpha coefficient. Validation was performed by checking the compliance of control for all operations on each of the stages (validation and transcription of the prescription, preparation, conservation, and administration) and by monitoring the operative control points and critical control points. ResultsThe results obtained from 387 bags were analyzed, with 30 interruptions of administration. The fulfillment of stages was 100%, including noncritical nonconformities in the storage control. The average deviation in the weight of the bags was less than 5%, and the infusion time did not present deviations greater than 1 hour. ConclusionsThe developed app successfully passed the evaluation and validation tests and was implemented to perform the monitoring procedures for the overall PN process. A new mobile solution to manage the quality and traceability of sensitive medicines such as blood-derivative drugs and hazardous drugs derived from this project is currently being deployed.